2004
DOI: 10.2135/cropsci2004.0936
|View full text |Cite
|
Sign up to set email alerts
|

Near Isogenic Lines Confirm a Soybean Cyst Nematode Resistance Gene from PI 88788 on Linkage Group J

Abstract: that Race 3 SCN resistance in PI 88788 is inherited by three genes, with one recessive and two dominant. The Soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is genetic evidence indicates that one of the dominant genes one of the most destructive soybean [Glycine max (L.) Merr.] pests is at a previously unreported locus which was designated worldwide. The most common source of SCN resistance used in soybean breeding in the northern USA is PI 88788. Previous research Rhg5 (Rao Arelli, 1994) the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 4 publications
(5 reference statements)
1
63
0
3
Order By: Relevance
“…, but its resistance to SCN races is inconsistent. A QTL was detected on LG J (Concibido et al, 1994(Concibido et al, , 1996(Concibido et al, , 1997 and was recently confirmed by means of near isogenic lines (Glover et al, 2004). LG B1 has been found to be associated with resistance to SCN but the locations of the QTLs declared are significantly inconsistent (Yue et al, 2001a(Yue et al, , 2001bVierling et al, 1996).…”
mentioning
confidence: 79%
“…, but its resistance to SCN races is inconsistent. A QTL was detected on LG J (Concibido et al, 1994(Concibido et al, , 1996(Concibido et al, , 1997 and was recently confirmed by means of near isogenic lines (Glover et al, 2004). LG B1 has been found to be associated with resistance to SCN but the locations of the QTLs declared are significantly inconsistent (Yue et al, 2001a(Yue et al, , 2001bVierling et al, 1996).…”
mentioning
confidence: 79%
“…Resistance to SCN is a multigenic trait and several genetic loci have been mapped [15,27-29,90-93]. Recently, the identity of genes residing at the rhg1 and Rhg4 loci have been reported [6-9] which confer some resistance to SCN.…”
Section: Discussionmentioning
confidence: 99%
“…Lander and Kruglyak (1995) indicated that there would be many regions with point-wise p value of 0.05 in one genome scan by chance and some will appear again in a second study just by chance. To reduce false positives, only QTLs at LOD $ 3.0 (point-wise p value # 0.001) were used in this study (Table 1), including QTLs detected by Glover et al (2004), and our studies (Guo et al, unpublished; Lu et al, unpublished). It is noted that most studies used SCN populations maintained at the University of Missouri-Columbia.…”
Section: Methodsmentioning
confidence: 99%
“…In previous soybean SCN-resistant QTL mapping studies, the following threshold levels were used for declaring QTL: (i) LOD 5 2.5 (equivalently p 5 0.003) (Yue et al, 2001a(Yue et al, , 2001b, (kii) p 5 0.002 (Concibido et al, 1994(Concibido et al, , 1996(Concibido et al, , 1997, and (iii) LOD 5 3 (equivalently p 5 0.001) (Webb et al, 1995;Heer et al, 1998;Qiu et al, 1999;Wang et al, 2001, Meksem et al, 2001. Few permutation tests were used to determine threshold levels (Glover et al, 2004). We used three methods to determine threshold value for declaring a QTL at the suggestive level (genome-wide type I error 5 0.63) and at the significant level (genome-wide type I error 5 0.05) for soybean F 2 mapping populations (used in the majority of studies).…”
Section: Classification Of Statistical Evidence Of Qtls Thresholds Fomentioning
confidence: 99%
See 1 more Smart Citation